Meningkatkan Kemampuan Guru dalam Menerapkan Model Pembelajaran Berdiferensiasi Melalui Supervisi Pembelajaran Di SDN Tondowulan 2 Plandaan Jombang - Wanisis Wanisis (Universitas Nusantara PGRI Kediri, 2023)
The objectives of this study are: (1) To describe the supervision of learning carried out in improving the ability of teachers to implement lesson plans using a differentiated learning model at SDN Tondowulan 2 Plandaan Jombang for the 2021-2022 academic year semester 2; (2) to describe the increase in the teacher's ability to apply a differentiated learning model after implementing learning supervision at SDN Tondowulan 2 Plandaan Jombang for the 2021-2022 academic year semester 2. This research is an action research (action research). The type of action research chosen is the emancipatory type. The research design used was the Kemmis model design which consisted of four steps, namely: planning, implementation, observation and reflection. The subjects of this research were teachers at SDN Tondowulan 2 Plandaan, totaling 10 teachers. The conclusions of this study: (1) Supervision of learning to improve teachers' ability to implement lesson plans using a differentiated learning model at SDN Tondowulan 2 Plandaan Jombang for the 2021-2022 academic year semester 2, carried out collaboratively by involving colleagues, supervisors and collaborators; (2) Increasing the ability of teachers to apply a differentiated learning model after implementing learning supervision at SDN Tondowulan 2 Plandaan Jombang for the 2021-2022 academic year semester 2, as seen from the acquisition of an average indicator score of 29.9 in the sufficient category in cycle I and an average score The average increased to 40 with a very good category in cycle II.